2013
DOI: 10.1111/resp.12205
|View full text |Cite
|
Sign up to set email alerts
|

Detection of viruses and atypical bacteria associated with acute respiratory infection of children in Hubei, China

Abstract: Background and objective Acute respiratory infection is the major cause of disease and death in children, particularly in developing countries. However, the spectrum of pathogenic viruses and atypical bacteria that exist in many of these countries remains incompletely characterized. The aim of this study was to examine the spectrum of pathogenic viruses and atypical bacteria associated with acute respiratory infection in children under the age of 16. Methods A total of 10 435 serum sera specimens were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 33 publications
5
27
2
1
Order By: Relevance
“…This difference might be attributed to the year of analysis or differences in the populations studied and methodology (10). Of the pathogens examined, MP was the most common pathogen detected (in 15.7 of the children), which was consistent with previous studies conducted in Nanjing and Wuhan, China (11,12).…”
Section: Discussionsupporting
confidence: 79%
“…This difference might be attributed to the year of analysis or differences in the populations studied and methodology (10). Of the pathogens examined, MP was the most common pathogen detected (in 15.7 of the children), which was consistent with previous studies conducted in Nanjing and Wuhan, China (11,12).…”
Section: Discussionsupporting
confidence: 79%
“…Our finding that the most commonly identified pathogen was M. pneumoniae (19.66 ) was similar to a study of hospitalized children in central China (19.1 ) and to a study of children and adults in southern China (16.9 ) (12,13). However, it was not consistent with a study of hospitalized children in southern China (13.2 ), where the most commonly identified pathogen was RSV (13.7 ) (14). This study found the positive detection rate of M. pneumoniae in 2016 was higher than that in 2015.…”
Section: Discussioncontrasting
confidence: 55%
“…Lymphocyte subset distributions by age are reported in Table 1 (percentages) and Table 2 (absolute counts 310 9 /L), which also list WBC and lymphocyte values. We tabulated the 10th and 90th percentiles, in addition to 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) 11 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) …”
Section: Resultsmentioning
confidence: 99%
“…First, establishing these ranges could contribute to the diagnosis of clinical disorders by serving as normal reference range values. Children younger than 7 years old are susceptible to suffering from bacteria and virus infections (22), bronchial asthma, and allergies (23). We applied flow cytometry in the clinic to test the immune status of children to common pediatric diseases, such as hand, foot and mouth disease (HFMD) (24), bronchopneumonia (25), asthma (26), idiopathic thrombocytopenic purpura(ITP) (27), and nephrotic syndrome (28).…”
Section: Introductionmentioning
confidence: 99%